The effect of media sterilization and varying sources and concentrations of sugar and nitrogen on alcohol production by Saccharomyces cereviseae strains - Halos, Saturnina C.; Lit, Aussielita L.; Cruz, Wilma T. (1987)
Several locally isolated and one ATCC yeast strains were tested for their ability to produce alcohol in sterilized and uninsterilized media, in various sugar sources, in varying sugar concentrations of molasses and in varying levels of nitrogen supplied by urea. Some strains produced alcohol only in sterilized media while other strains poduced much or sometimes higher alcohol when media was unsterilized. Molasses was the best source of sugar for all strains except MG2065 which produced as much alcohol from brown sugar. All strains except MG2064 produced the highest alcohol concentration at 10% sugar concentration while nitrogen from urea supplied at 10% mg/L was equipped for alcohol for production in unsterilized media.
Includes bibliographical references (page 77)
Keywords: Biological Sciences; Molasses -- Culture media; Alcohol -- Production; Saccharomyces cereviseae -- Alcohol production